Data: Dynamic Graphical Instructions Result in Improved Attitudes and Decreased Task Completion Time in Human–Robot Co-Working: An Experimental Manufacturing Study - Eimontaite, Iveta; Cameron, David (Cranfield University, 2023)
This study explores how dynamic graphical signage could aid a manufacturing task. Forty employees from one UK manufacturing company participated in a field experiment to complete a precision pick-and-place task working in conjunction with a collaborative robotic arm. Twenty-one participants completed the task with the support of dynamic graphical signage that provided information about the robot and the activity, while the rest completed the same task with no signage. Participants accuracy, response time, negative attitudes to robot, and outcome expectancy were assessed in this study. Data from: Eimontaite, I.; Cameron, D.; Rolph, J.; Mokaram, S.; Aitken, J.M.; Gwilt, I. Dynamic GraphicalInstructions Result in ImprovedAttitudes and Decreased TaskCompletion Time in Human–Robot Co-Working: An ExperimentalManufacturing Study. Sustainability 2022, 14
Keywords: human-robot collaboration'; 'graphical sigange'; 'manufacturing task performance'; 'attitudes towards robots'; 'technology acceptance'; 'Applied Psychology'